VEGETABLE CROP DISEASES AND THEIR CONTROL MEASURES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
Vegetable crop diseases are a major constraint on global production, causing significant yield and quality losses. The main pathogens include fungi, bacteria, viruses, and nematodes, which lead to wilting, leaf spots, root rot, and other plant damages. Effective disease management requires an integrated approach combining cultural practices, resistant varieties, and chemical and biological control measures. Integrated disease management minimizes crop losses, reduces pathogen pressure, and limits environmental impact. Recent research highlights the importance of early diagnosis, pathogen monitoring, and the adoption of innovative technologies to enhance crop resilience. Overall, the implementation of comprehensive control strategies contributes to sustainable vegetable production, improved crop quality, and strengthened food security.